Football and discrimination: Antisemitism and beyond - Brunssen, Pavel; Schüler-Springorum, Stefanie (Routledge, 2021)
"This book takes a close look at discrimination in football in order to illuminate our understanding of the interaction between sport and wider society, politics and culture, particularly in terms of the (re)production of identity. It presents fascinating and diverse international case studies, including the shadow of fascism in Italian football; fan activism against racism, sexism and homophobia in US soccer; migrant football clubs in Germany, and the use of football club history in the teaching of antisemitism. Together they demonstrate the damaging societal consequences of unchecked resentment and discrimination in football fan cultures but also the potential for fan activism as a socio-positive force. This is fascinating reading for anybody with an interest in football or fandom, the sociology of sport, cultural studies, or political science"--
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Rassismus; Antisemitismus; Diskriminierung; Gruppenidentität; Fußball